Postawy interpersonalne młodzieży wobec edukacji międzykulturowej - Garbuzik, Paweł (Uniwersytet Rzeszowski, 2022)
Przedmiotem rozprawy są postawy interpersonalne młodzieży szkół ponadpodstawowych wobec edukacji międzykulturowej z terenu miasta Kielce i powiatu kieleckiego województwa świętokrzyskiego. Głównym jej celem jest odpowiedź na pytanie jakie są postawy interpersonalne młodzieży wobec edukacji międzykulturowej? Praca dostarcza odpowiedzi na szereg szczegółowych pytań dotyczących postaw młodzieży wobec edukacji międzykulturowej, uwzględniając trzy komponenty postaw, tj. poznawczy, emocjonalny i behawioralny, mianowicie: Jaka jest ocena wiedzy o innych kulturach, mniejszościach narodowych i etnicznych? Jakie były cele realizowanych zajęć (treści) z zakresu edukacji międzykulturowej? Jaki jest poziom tolerancji wobec „innych” oraz co wnosi obecność przedstawicieli innych kultur, mniejszości narodowych i etnicznych? Jakie są cechy relacji z przedstawicielami innych kultur, mniejszości narodowych i etnicznych? Czy szkoły ponadpodstawowe podejmują inicjatywy na rzecz integracji uczniów z innych kultur, mniejszości narodowych i etnicznych i jakie są ich implikacje?

The subject of the dissertation is the interpersonal attitudes of secondary school students towards intercultural education from the city of Kielce and the Kielce poviat of the Świętokrzyskie Voivodeship. Its main goal is to answer the question what are the interpersonal attitudes of young people towards intercultural education? The work provides answers to a number of detailed questions regarding the attitudes of young people towards intercultural education, taking into account three components of attitudes, i.e. cognitive, emotional and behavioral, namely: What is the assessment of knowledge about other cultures, national and ethnic minorities? What were the goals of the activities (content) in the field of intercultural education? What is the level of tolerance towards "others" and what does the presence of representatives of other cultures, national and ethnic minorities bring? What are the characteristics of the relationship with representatives of other cultures, national and ethnic minorities? Do secondary schools undertake initiatives to integrate students from other cultures, national and ethnic minorities and what are their implications?
Interpersonal attitudes of youth towards intercultural education
Promotor: dr hab. Mirosław Z. Babiarz, prof. UJK - 227 s.
Keywords: zróżnicowanie; międzykulturowość; postawy; młodzież; diversity; interculturalism; attitudes; youth; education; edukacja